Agreement between the United Kingdom of Great Britain and Northern Ireland and the Secretariat of the United Nations Framework Convention on Climate Change, the Kyoto Protocol and the Paris Agreement regarding the twenty-sixth session of the Conference of the Parties to the United Nations Framework Convention on Climate Change, the sixteenth session of the Conference of the Parties serving as the meeting of the Parties to the Kyoto Protocol, the third session of the Conference of the Parties serving as the meeting of the Parties to the Paris Agreement and the sessions of the subsidiary bodies, Manchester and Bonn, 5 October 2021 and London and Bonn, 8 and 11 October 2021. ([2021-10-28]) - Unknown
No abstract available